2017
DOI: 10.1111/eci.12725
|View full text |Cite
|
Sign up to set email alerts
|

Soluble transferrin receptor and risk of type 2 diabetes in the obese and nonobese

Abstract: The association between sTfR levels and risk of T2DM in a population at high cardiovascular risk depend on the presence or absence of obesity. While in nonobese subjects elevated sTfR levels are associated with a decreased risk of developing T2DM, in obese subjects the risk increases. This suggests that obesity alters the relationship between sTfR and T2DM incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…However, our finding of the positive association between sTfR and CKD is consistent with Alam et al, who observed high sTRF levels in patients with CKD than those without CKD (27). This association can also be comparable with previous observations that increased level of sTfR had adverse effects on different health outcomes, including diabetes or insulin resistance (15,32), iron-deficiency anemia (33), and obesity (34). In this study, we also found a U-shaped relationship of Hb and CKD, which is comparable with findings from other health outcomes, such as mortality (35), birth outcome (36), and stroke severity (14).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our finding of the positive association between sTfR and CKD is consistent with Alam et al, who observed high sTRF levels in patients with CKD than those without CKD (27). This association can also be comparable with previous observations that increased level of sTfR had adverse effects on different health outcomes, including diabetes or insulin resistance (15,32), iron-deficiency anemia (33), and obesity (34). In this study, we also found a U-shaped relationship of Hb and CKD, which is comparable with findings from other health outcomes, such as mortality (35), birth outcome (36), and stroke severity (14).…”
Section: Discussionsupporting
confidence: 92%
“…Serum ferritin (SF), soluble transferrin receptor (sTfR), hemoglobin (Hb), and transferrin are the most widely used clinical biomarkers of iron. Previous publications have reported the relationships between these markers with hypertension (12), hyperuricemia (13), stroke (14), and diabetes (15). However, there are limited studies evaluating whether iron levels are associated with estimated glomerular filtration rate (eGFR)/CKD in general population.…”
Section: Introductionmentioning
confidence: 99%
“…Of these studies, 145 were from PubMed and 23 from Embase; 23 repeated studies were excluded. After skimming the titles and abstracts, followed by an intensive reading of the full text, 12 case–control studies and cohort studies were obtained, which included 6,516 patients with type 2 diabetes and 43,120 control individuals without type 2 diabetes. The details of the screening process are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, more than 80% to 90% of T2DM patients are obese. [ 22 ] The excess body weight influences almost every aspect of life and it is difficult to treat the overweight in T2DM patients. Therefore, weight management is of great significance to patients with obese T2DM.…”
Section: Discussionmentioning
confidence: 99%